A nova televisão: estratégias, desafios e tendências da distribuição digital não linear no mercado brasileiro - Martins, João Paulo Bulhões Nogueira (2020)
The consumption of audiovisual content has been through a deep transformation in the last ten years. Technology evolution and cultural changes affected audience behavior in a way that put the traditional linear programming model (free-to-air and Pay TV) in check by advertisers, production companies and the audience. This dissertation analyzes the conjuncture of this market, focusing on video on demand services, specifically the three leading platforms of this segment in Brazil (Netflix, YouTube and Globoplay). In order to build this analysis, seven media and technology experts gave their testimonies about the strategies and challenges of the Brazilian scenario. In in- depth interviews, each of them indicated and described the most relevant attributes of each platform and the video streaming environment. The executives and specialists also highlighted the main trends and next steps, as well as aspects such as content piracy and competition. The results indicate that today’s market presents opportunities and increasing interest of new players, although there is already a solid number of video streaming services consumers in Brazil. In addition, there are relevant local infrastructure challenges in telecommunications and share of time competition between on demand, free-to-air TV, pay TV and the gaming segment. Concerning market trends of this creative industry sector, there is a convergent scenario between streaming platforms, social networks and traditional media. An additional subject of analysis is the probable increase in local content production as driving force for brand awareness, conversion and user loyalty. As a managerial contribution and practical application, this study broadens the discussion about the audiovisual industry. It also deepens the knowledge about the video on demand segment, improving the understanding of the leading players, their different positioning and monetization strategies